2017
DOI: 10.3847/1538-4357/834/2/102
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Fossil Evidence of Agn Feedback in Wise-Selected Stripe-82 Galaxies by Measuring the Thermal Sunyaev–zel’dovich Effect With the Atacama Cosmology Telescope

Abstract: We directly measure the thermal energy of the gas surrounding galaxies through the thermal Sunyaev-Zel'dovich (tSZ) effect. We perform a stacking analysis of microwave background images from the Atacama Cosmology Telescope, around 1179 massive quiescent elliptical galaxies at 0.5 ≤ z ≤ 1.0 ("low-z") and 3274 galaxies at 1.0 ≤ z ≤ 1.5 ("high-z"), selected using data from the Wide-Field Infrared Survey Explorer All-Sky Survey and the Sloan Digital Sky Survey (SDSS) within the SDSS Stripe-82 field. The gas surrou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 131 publications
(155 reference statements)
1
15
1
Order By: Relevance
“…Our assumption linking the amplitude of the SZ effect to the bolometric luminosities of quasars indicates a lower signal for the thermal SZ effect around lower redshift quasars. This is contrary to what might be expected when considering the detection of fossil feedback energy due to the long cooling times in quasar dark matter halos (Planck Collaboration et al 2013;Greco et al 2015;Spacek et al 2016Spacek et al , 2017Spacek et al , 2018Tanimura et al 2019;Pandey et al 2019). However, if we consider that quasars are a phase in galaxies' evolution (Hopkins et al 2005b), then the quasars that we observe at lower redshifts may not have been quasars at high redshift.…”
Section: Implications For Quasar Feedbackcontrasting
confidence: 90%
See 1 more Smart Citation
“…Our assumption linking the amplitude of the SZ effect to the bolometric luminosities of quasars indicates a lower signal for the thermal SZ effect around lower redshift quasars. This is contrary to what might be expected when considering the detection of fossil feedback energy due to the long cooling times in quasar dark matter halos (Planck Collaboration et al 2013;Greco et al 2015;Spacek et al 2016Spacek et al , 2017Spacek et al , 2018Tanimura et al 2019;Pandey et al 2019). However, if we consider that quasars are a phase in galaxies' evolution (Hopkins et al 2005b), then the quasars that we observe at lower redshifts may not have been quasars at high redshift.…”
Section: Implications For Quasar Feedbackcontrasting
confidence: 90%
“…This has been done for massive elliptical systems (with halo mass ∼ 10 14 M ) associated with luminous red galaxies (Hand et al 2011). Others observed systems with halo mass ∼ 10 13 M that have characteristic total energies of 7 × 10 61 ergs in the circumgalactic medium (Planck Collaboration et al 2013;Greco et al 2015;Spacek et al 2016Spacek et al , 2017Spacek et al , 2018Tanimura et al 2019;Pandey et al 2019). These latter studies aim to detect fossil energy from past AGN activity -coincidentally of the same order as the cluster feedback energy scale quoted above.…”
Section: Introductionmentioning
confidence: 99%
“…However, the AGN feedback-induced tSZ is expected to be too feeble to be detected at the single source level, therefore one must resort to statistical techniques such as cross-correlation and stacking. The first tentative detection of tSZ due to AGN feedback effect was reported by Chatterjee et al (2009), while subsequent works by Ruan et al (2015); Crichton et al (2016); Verdier et al (2016); Spacek et al (2016Spacek et al ( , 2017; Soergel et al (2017) found evidence of this effect at different significance levels. However, there is no general consensus as the inferred thermal energies differ substantially among the various studies.…”
Section: Future Outlookmentioning
confidence: 94%
“…Here, we are explicitly focused on tSZ stacking or cross-correlation analyses on halo samples. 2 Similar analyses have also been performed for massive elliptical galaxies (rather than quasars)[41,42].…”
mentioning
confidence: 93%